Problematika Metode Pengajaran dalam Pendidikan Islam Modern - Soleha, Zachro; Sukari, Sukari (Lembaga Yasin AlSys, 2024)
Teaching methods play an important role in achieving educational goals, including in modern Islamic education. However, in practice, there are a number of problems faced by educators. With a literature study approach, this paper aims to identify and analyze various challenges that arise in the application of teaching methods in modern Islamic education, such as the gap between the curriculum and social reality, the dominance of conventional teaching methods that are less interactive, and the limited use of technology. The influence of globalization and technological developments also affect student learning patterns and pose new challenges in maintaining Islamic identity and values. To overcome these problems, innovation is needed in teaching methods, integration of technology in learning, alignment of the curriculum with the needs of the times, and improvement of the quality of educators. Thus, modern Islamic education can be more relevant and effective in forming a generation of Muslims who are noble, intelligent, and able to compete in the global era.